Sustainability of the Indian auto rickshaw sector: identification of enablers and their interrelationship using TISM. (2018) - Behl, Abhishek; Rathi, Paridhi; Kumar, V.V. Ajith
The present study is an attempt to identify the enablers to the sustainability of the auto rickshaw sector in India and model them using interpretive structural modelling (ISM) in order to establish inter relationships among them. Matriced' Impacts Croises-Multiplication Appliqué an Classment (MICMAC) analysis has been applied to identify the most dominant enabler(s). A total of 11 enablers have been identified from the extant literature. The resultant ISM model with four levels of hierarchy reveals that not all enablers require the same attention - the four enablers at the very bottom, namely 'Fleet-based operations', 'Adequate transport infrastructure', 'Robust planning and regulatory structure' and 'Adequate enforcement and monitoring' are the ones that drive most other enablers. Accordingly, the mix of fleet-based operations along with information and communications technology (ICT) infrastructure assumes urgency for enhancing door to door mobility and first and last mile connectivity of auto rickshaws. In addition, regulations pertaining to permits, emissions and safety also need urgent attention.